2021
DOI: 10.1155/2021/6691459
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transcutaneous Electrical Acupoint Stimulation on Postoperative Catheter-Related Bladder Discomfort in Patients Undergoing Transurethral Resection of the Prostate

Abstract: Background. Catheter-related bladder discomfort (CRBD), an extremely distressing complication secondary to an indwelling urinary catheterization, is frequently reported in patients with transurethral resection of the prostate (TURP), postoperatively. A prospective, randomized, controlled, double-blind study was designed to assess the efficacy of transcutaneous electrical acupoint stimulation (TEAS) as a treatment for CRBD in patients undergoing TURP. Methods. Seventy benign prostatic hyperplasia male patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
0
12
0
6
Order By: Relevance
“…BL32 and BL33 belong to the Bladder meridian, and according to TCM this meridian and acupoints mainly treat diseases associated with the urinary system (12) . It is suggested that through these acupoints there is stimulation of the sacral nerves, detrusor, and pelvic muscles to regulate the function of the bladder, urethral sphincter and nerve innervation effector (12)(13)(14) . Stimulation of these acupoints increases the resistance of the urethra and pelvic floor muscles (14) making them essential for urinary continence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BL32 and BL33 belong to the Bladder meridian, and according to TCM this meridian and acupoints mainly treat diseases associated with the urinary system (12) . It is suggested that through these acupoints there is stimulation of the sacral nerves, detrusor, and pelvic muscles to regulate the function of the bladder, urethral sphincter and nerve innervation effector (12)(13)(14) . Stimulation of these acupoints increases the resistance of the urethra and pelvic floor muscles (14) making them essential for urinary continence.…”
Section: Discussionmentioning
confidence: 99%
“…To produce a protocol of points that could help other acupuncturists to treat not only the symptoms, but also the root cause of PRPUI, in addition to the points referred to as the most used (BL23, BL28, BL32, BL33, ST36, SP6) (12)(13)(14)29,30) , points BL13, BL15, BL18, BL20 and LV5 were used which, according to TCM, have effects on the possible causes of prostate cancer. It was noted that the use of these lumbosacral and leg region acupoints showed clinically significant benefits in reducing PRPUI.…”
Section: Discussionmentioning
confidence: 99%
“…Essa ciência defende que todas as funções do corpo são reguladas para manter um equilíbrio de Qi, e o desvio, portanto, é descrito como doença. Qi é a energia vital que circula dentro do indivíduo, que mantém o funcionamento dos órgãos e, portanto, promove a manutenção da vida (5,12) . Assim, no caso de IU, o reequilíbrio deve ser feito nos meridianos que influenciam a continência urinária (5,12) .…”
Section: Introductionunclassified
“…Qi é a energia vital que circula dentro do indivíduo, que mantém o funcionamento dos órgãos e, portanto, promove a manutenção da vida (5,12) . Assim, no caso de IU, o reequilíbrio deve ser feito nos meridianos que influenciam a continência urinária (5,12) . Os pontos de acupuntura (acupontos), dispostos ao longo dos canais por onde circula o Qi (meridianos), são estimulados com a inserção de finas agulhas para equilibrar o Qi e, consequentemente, prevenir ou tratar a doença e seus sintomas (5) .…”
Section: Introductionunclassified
See 1 more Smart Citation